Criterios normativos para la presentación de originales de la Revista General de Información y Documentación - Muñoz-alonso López, Gemma (Revista General de Información y Documentación, 2004)
This article, divided into four chapters, deals with some of the factors that influence the impact of academic periodical publications. The introduction draws attention to the urgent need for unification of standards concerning the way in which scientific knowledge is transmitted. "Materiales y métodos: criterios para elaborar normas de publicación" describes the parameters that should be followed by the Revista General de Información y Documentación of the Complutense University in Madrid in order to adapt to the new national and international requirements so as to be able to offer information of a high level and quality. With "Resultados: implementación del sistema Harvard en la Revista General de Información y Documentación" the criteria of the Harvard system for quotation is applied and several examples are given. Finally, "Discusión de los resultados: diferentes niveles de documentos normativos", reviews the documentation most used in the field of academic writing standardization, and also some of the more pertinent ISO regulations for achieving formal quality of manuscripts in the diffusion of intellectual production.
Keywords: Harvard system; Knowledge diffusion; Periodical publications; Publication standards; Revista General de Información y Documentación